The role of tidal creeks in shaping carbon and nitrogen patterns in a Chinese salt marsh - Ma, Ziwen; Wu, Yanan; Zhao, Siqi; Pan, Yueyan; Liu, Jiakai; Zhang, Mingxiang; Zhang, Zhenming (Frontiers in Marine Science, 2024)
Tidal creeks play a crucial role in lateral transport of carbon and nutrients from tidal salt marshes. However, the specific impact of tidal creek development on carbon and nutrient distribution within the marsh remains poorly understood. The objective of this study is to assess the influence of lateral tidal flooding through the tidal creeks on the spatial distribution of carbon and nitrogen fractions in the soils of a Chinese temperate salt marsh. We conducted a comprehensive analysis of the relative variations in different carbon and nitrogen fractions, along with soil physicochemical and microbial indicators, between the bank soil of the tidal creek and its lateral inland soils across high, middle, and low flats. Our findings highlight that tidal creek development significantly affects the middle flat, leading to substantial variations in organic carbon and total nitrogen. The low flat mainly experiences changes in dissolved inorganic carbon levels. Furthermore, a lateral increase in microbial biomass is observed in the middle flat, indicating that the significantly lower SOC in the middle flat might be ascribed to enhanced microbial decomposition. The lateral enrichment of dissolved inorganic carbon in the low flat is possibly related to the nearshore location and/or abiotic adsorption in inorganic carbon sequestration.Overall, this study demonstrates the critical role of tidal creek development in shaping the distribution patterns of carbon and nitrogen fractions in tidal salt marshes.